A cycloalkyl-substituted symmetrical α-diimine nickel complex, preparation method and use thereof

By designing a cycloalkyl-substituted symmetric α-diimine nickel complex, the problem of poor tolerance of existing catalysts in polar monomer polymerization is solved, high catalytic activity and thermal stability are achieved, and it is suitable for the preparation of high-performance polyethylene elastomers.

CN116396338BActive Publication Date: 2025-04-29CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310369517.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-07
Publication Date
2025-04-29
Estimated Expiration
2043-04-07

Smart Images

  • Figure CN116396338B_ABST
    Figure CN116396338B_ABST
Patent Text Reader

Abstract

The present invention provides a nickel complex represented by formula (I), wherein R is the same or different and is independently selected from cyclopentyl, cyclohexyl, cyclooctyl or cyclododecyl; X is the same or different and is independently selected from F, Cl, Br or I. The nickel complex contains cycloalkyl substituents with different steric hindrances and another large steric hindrance substituent diphenylmethyl, and exhibits a single catalytic active center. The molecular weight of the polymer can be precisely controlled by adjusting the structure of the catalyst and the polymerization reaction conditions. The complex can be used to prepare polyethylene rich in short-chain branches, and has the advantages of high catalytic activity and low synthesis cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyolefin catalysts, and in particular to a cycloalkyl-substituted symmetrical α-diimine nickel complex, a preparation method and application thereof. Background Art

[0002] Polyethylene (PE for short) is a thermoplastic resin material made by polymerizing ethylene monomers. It is the largest type of polyolefin material in terms of output and plays a key role in the development of this field. Thermoplastic elastomers have the elasticity of rubber materials at room temperature and can be plasticized at high temperatures. They are a new type of polymer elastic material between resin and rubber, with good mechanical properties and high cost performance. This type of material has excellent processing performance and is widely used in many fields such as clothing, adhesives, electronics and their components.

[0003] As a key link in the research of ethylene polymerization, the structure of olefin polymerization catalyst determines the microstructure and mechanical properties of polyethylene chain. At present, catalysts with different catalytic characteristics, such as ZN, Phillips and metallocene catalysts, have been designed, developed and widely used. However, due to the strong affinity of early transition metals, they are easy to form stable chelates with heteroatoms in polar monomers, which makes this type of catalysts have poor tolerance to polar monomers and easy to be poisoned and deactivated; at the same time, the catalytic reaction dominated by heterogeneous catalysts is difficult to control, so the practicality of early transition metal catalysts in olefin polymerization is greatly limited. The corresponding late transition metals not only have weak affinity for oxygen, but also have high stability, simple synthesis and low cost, and are much less restricted in development. As a typical representative of late transition metal catalysts, homogeneous nickel (II) catalysts can realize the polymerization of pure ethylene monomers into thermoplastic elastomer materials without adding α-olefins. In order to further promote the development of polyethylene in industrial technology and high-end applications, the structural modification of the α-diimine ligand skeleton and the design and development of catalysts with adjustability and thermal stability in catalyzing olefin polymerization are the key points to achieve this goal.

[0004] Based on previous polymerization results, polyethylene produced by nickel (II) catalysts has high branching degree, low melting point (generally below 110°C), good mechanical properties such as tensile strain and elastic recovery. This is because during the ethylene polymerization process, α-diimine nickel (II) complexes promote ethylene monomers to eliminate and reinsert β-H in a unique "chain walking" manner, forming branched / hyperbranched polyethylene with thermoplastic elastomer properties. In addition, this type of nickel complex catalyst can regulate the microstructure and properties of polyethylene products, including various indicators such as branching degree, crystallinity, melting point, density and hardness, by adjusting its own structure and changing the temperature and ethylene pressure during the polymerization reaction. In addition, when an alkyl aluminum reagent is used as a co-catalyst for activating ethylene polymerization, the operating temperature of the polymerization is 30-40°C, and the ethylene pressure reaches 10 atm, the optimal activity level of the nickel complex catalyst AD listed in Formula 1 (Formula 1, A, Polym. Chem., 2022, 13, 1040-1058; B, Appl Organometal Chem. 2019; 33: e4749; C, Catalysis Science & Technology, 2013, 3, 2737-2745; D, Applied Catalysis A: General, 2014, 475, 195-202) can reach 10 6 g(PE)mol(Ni) -1 h -1 Specifically, taking the catalyst system in Formula 1 as an example, the catalytic activity of A can be as high as 21.0×10 6 g(PE)mol(Ni) -1 h -1 The catalytic activity of B is 10.6×10 6 g(PE)mol(Ni) -1 h -1 The catalytic activity of C is 5.49×10 6 g(PE)mol(Ni) -1 h -1 On this basis, the C structure was further modified to obtain D, and its catalytic activity was also improved to 8.19×10 6 g(PE)mol(Ni) -1 h -1 , and most of the catalytic systems based on α-diimine structure can obtain branched polyethylene with a relative molecular weight of up to hundreds of thousands.

[0005]

[0006] In order to develop branched polyethylene products with better performance, especially polyethylene products rich in short chain branches, the study of the structure of ethylene polymer catalysts has become a key link in ethylene polymerization research. This field needs to further control the catalyst structure by controlling the type of catalyst center metal, metal valence and the structure of the ligand such as electronic effect and stereo effect, so as to further improve the catalytic performance and thermal stability of the catalyst, as well as improve the conditions and efficiency of its preparation method. Summary of the invention

[0007] Based on the potential adjustability of the ring size and steric hindrance of the cycloalkyl substituents, the present invention studies the influence of the cycloalkyl substituents on the catalytic activity of the catalyst and the structural characteristics of polyethylene, and further explores the regulation mode of the catalytic performance of the catalyst system by the systematic modification of the ligand structure.

[0008] The inventors are committed to the design and development of olefin polymerization catalysts, and have conducted detailed research on the catalytic processes corresponding to the catalysts. So far, a lot of related work has been done around the [N^N], [N^N^N] and [N^O] type ligand structures and the complex catalysts after complexation with late transition metals. Based on these studies, it is found that the catalytic performance of ethylene polymerization catalysts can be regulated by modifying the ligand skeleton and the N-aryl substituent structure, and the results obtained have also been recognized and paid much attention by international peers. On this basis, improving the catalytic performance and thermal stability of the catalyst has also become a further research goal. Therefore, in the invention, based on the classic α-diimine [N^N] ligand structure, the inventors stabilized the α-diimine ligand structure by introducing a cycloalkyl substituent group with certain spatial flexibility on the N-aryl group, and at the same time combined with the large sterically hindered diphenylmethyl group at the ortho / para position to modify the steric effect of the ligand. The relevant research results can provide a high reference and guiding value for the design and development of nickel-based catalysts with controllability and high performance.

[0009] Based on the above research objectives, one of the objects of the present invention is to provide a nickel complex as shown in the following formula (I):

[0010]

[0011] Wherein, R is the same or different, and each is independently selected from cyclopentyl, cyclohexyl, cyclooctyl or cyclododecyl; X is the same or different, and each is independently selected from F, Cl, Br or I.

[0012] According to the nickel complex represented by formula (I) of the present invention, the nickel complex represented by formula (I) is selected from the following nickel complexes, but is not limited to the following nickel complexes:

[0013] Nickel complex 1: wherein R is cyclopentyl and X is Br;

[0014] Nickel complex 2: R is cyclohexyl and X is Br;

[0015] Nickel complex 3: R is cyclooctyl and X is Br;

[0016] Nickel complex 4: wherein R is cyclododecyl and X is Br.

[0017] The second object of the present invention is to provide a method for preparing the nickel complex represented by the above formula (I), comprising the following steps:

[0018]

[0019] The compound represented by formula (II), the compound represented by formula (III) and the nickel-containing compound are mixed and stirred in a solvent to react to obtain the nickel complex represented by formula (I).

[0020] wherein R and X are as defined above.

[0021] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the nickel-containing compound is selected from nickel-containing halides, hydrates or solvates of nickel-containing halides, such as NiCl2·6H2O or NiBr2·DME, preferably NiCl2·6H2O.

[0022] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the molar ratio of the compound represented by formula (II) to the compound represented by formula (III) is 1:(2-4), preferably 1:4.

[0023] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the molar ratio of the nickel-containing compound to the compound represented by formula (II) is 1:(1-1.5), preferably 1:1.

[0024] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the solvent is a weakly acidic organic solvent, for example, formic acid or acetic acid, preferably acetic acid.

[0025] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the molar volume ratio (mmol / mL) of the compound represented by formula (II) to the solvent is 1:(25-100), for example, 1:100, 1:80, 1:50, 1:25.

[0026] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the reaction temperature is 60-120° C., preferably 110-120° C.; the reaction time is 4-6 hours, preferably 4-5 hours.

[0027] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the reaction is carried out under anaerobic conditions, for example, under the protection of an inert gas (such as nitrogen).

[0028] According to the method for preparing the nickel complex represented by formula (I) of the present invention, after the reaction is completed, the reaction solution is concentrated under reduced pressure to remove the solvent to obtain a residue, the residue is dissolved with a good solvent, and then a poor solvent is added for recrystallization to precipitate a solid, which is filtered, washed, and dried to obtain the product.

[0029] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the volume ratio (mL / mL) of the good solvent to the poor solvent is 1:10-1:50, preferably 1:10-1:40; more preferably 1:15-1:30; for example, 1:25.

[0030] According to the method for preparing the nickel complex represented by formula (I) of the present invention, the good solvent is toluene or dichloromethane, preferably dichloromethane; the poor solvent is ether, n-hexane or n-heptane, preferably anhydrous ether.

[0031] The third object of the present invention is to provide a catalyst composition, which includes a main catalyst and an optional co-catalyst, wherein the main catalyst is a nickel complex as shown in the above formula (I).

[0032] According to the catalyst composition of the present invention, the co-catalyst is selected from one or more of aluminoxane, alkylaluminum and alkylaluminum chloride.

[0033] According to the catalyst composition of the present invention, the aluminoxane is methylaluminoxane (MAO) and / or triisobutylaluminum-modified methylaluminoxane (MMAO), the alkylaluminum is trimethylaluminum (AlMe3), and the alkylaluminum chloride is one or more of diethylaluminum monochloride (Et2AlCl, DEAC), triethylaluminum trichloride (EASC) or ethylaluminum dichloride (EtAlCl2, EADC).

[0034] According to the catalyst composition of the present invention, when the catalyst composition includes a co-catalyst, the molar ratio of the metal Al in the co-catalyst to the central metal Ni of the nickel complex shown in formula (I) is (200-3000):1, and the preferred molar ratio is (300-2500):1, for example, 300:1, 400:1, 500:1, 600:1, 700:1, 1500:1, 1750:1, 2000:1, 2250:1, 2500:1.

[0035] According to the catalyst composition of the present invention, when the co-catalyst is aluminoxane, it is preferably methylaluminoxane (MAO), and the molar ratio of the metal Al in the co-catalyst to the central metal Ni of the nickel complex shown in formula (I) is (1500-2500):1, preferably the molar ratio is 2000:1.

[0036] According to the catalyst composition of the present invention, when the co-catalyst is an alkylaluminum chloride, preferably diethylaluminum monochloride (DEAC) and ethylaluminum dichloride (EADC), the molar ratio of the metal Al in the co-catalyst to the central metal Ni of the nickel complex shown in formula (I) is (300-700):1, preferably the molar ratio is 500:1.

[0037] A fourth object of the present invention is to provide a method for preparing polyethylene, comprising: carrying out an ethylene polymerization reaction under the action of the catalyst composition as described above to obtain polyethylene.

[0038] According to the method for preparing polyethylene of the present invention, the temperature of the polymerization reaction is 20-70°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C or 70°C; the time of the polymerization reaction is 5-120min, for example, 5min, 15min, 30min, 45min, 60min, 70min, 80min, 90min, 100min, 110min or 120min; the pressure of the polymerization reaction is 0.3-20atm, for example, 1atm, 5atm, 10atm, 15atm or 20atm.

[0039] According to the method for preparing polyethylene of the present invention, the solvent used in the polymerization reaction is selected from one or more of toluene, o-xylene, n-hexane or cyclohexane, preferably toluene.

[0040] A fifth object of the present invention is to provide the use of the nickel complex represented by the above formula (I) in the preparation of polyolefin, wherein the polyolefin is preferably polyethylene.

[0041] Beneficial Effects

[0042] 1. The present invention provides a type of cycloalkyl-substituted symmetrical α-diimine nickel complexes that can be used to prepare polyethylene elastomers rich in methyl branches. This type of nickel complex contains cycloalkyl substituents with different steric hindrances and another large steric hindrance substituent diphenylmethyl, which exhibits a single catalytic active center, and can achieve precise control of polymer molecular weight by adjusting the structure of the catalyst and the polymerization reaction conditions, and has the advantages of high catalytic activity and low synthesis cost. When the polymerization reaction is activated by the cocatalyst ethylaluminum dichloride (EADC), the catalyst exhibits the best catalytic activity at an operating temperature of 30°C [10.3×10 6g(PE)mol(Ni) -1 h -1 ], after 60 min of reaction, the catalytic activity was still maintained at 9.24×10 6 g(PE)mol(Ni) -1 h -1 When the catalyst was activated with the cocatalyst diethylaluminum chloride (DEAC), the best catalytic activity [10.7×10 6 g(PE)mol(Ni) -1 h -1 ]. The cocatalyst methylaluminoxane (MAO) was found to be the most effective cocatalyst, with the best catalytic activity reaching [13.2×10 6 g(PE)mol(Ni) -1 h -1 ], and the catalytic activity was maintained at 6.54-11.6×10 6 g(PE)mol(Ni) -1 h -1 In summary, under the activation of different types of co-catalysts, this type of nickel complex catalyst can maintain high catalytic activity and have a long polymerization cycle. Therefore, this type of α-diimine nickel complex catalyst with high catalytic activity and high thermal stability has a very promising prospect for industrial application.

[0043] 2. The present invention provides a method for preparing a high-performance nickel complex for producing polyethylene elastomers, and the advantages of the preparation process are good thermal stability of the catalyst, long catalytic cycle, simple operating conditions, etc.

[0044] 3. The present invention provides the use of such nickel complexes, which can be used as a main catalyst for novel olefin polymerization, and are particularly suitable for ethylene polymerization. Such nickel complexes have the following structural characteristics: different cycloalkyl substituents are introduced at the 6-position on the aromatic groups on both sides of the α-diimine to regulate the steric hindrance and electronic effect of the nickel metal center, and the substituents at the 2-position and 4-position are fixed as bulky substituents, diphenylmethyl. Under the synergistic effect of these specific structures, the suitable large steric hindrance environment at the ortho position protects the metal active center to a certain extent, inhibits the occurrence of chain transfer and chain termination, and is conducive to the monomer insertion reaction. In the polyethylene chain generated under the polymerization conditions showing the best catalytic activity, there are 73 to 104 branches per 1000 carbon atoms, and it is more inclined to generate polyethylene elastomers rich in short branches (Me%>80%). After the polyethylene sample obtained at a reaction temperature of 60°C was compression-molded, the breaking strain of the sample strip could reach up to 861%, and the corresponding ultimate tensile stress reached 8.59MPa. It also had good elastic recovery ability (SR≥60.5%), which is close to the performance parameters of propylene-based POE. This shows that it can be used as a new energy-saving material to replace propylene-based POE and further used in PP modification, film / sole material manufacturing, etc.

[0045] 4. The method for preparing polyethylene elastomer provided in the present invention has a simple process and mild operating conditions, and can be used to prepare polyethylene elastomer rich in short chain branches. The molecular weight of the obtained polymer is 3.69-15.0×10 5 g·mol -1 The molecular weight of the obtained polymer fluctuates between 36.7 and 104.6 °C, and the molecular weight distribution M w / M n Between 1.9-3.3. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the molecular structure of single crystal analysis of Ni2 prepared in Example 2 of the present invention.

[0047] Figure 2 Schematic diagram of the molecular structure of single crystal analysis of Ni4 prepared in Example 4 of the present invention.

[0048] Figure 3 This is the temperature-elevated NMR carbon spectrum of the polyethylene prepared in Example 5a) of the present invention.

[0049] Figure 4 This is the temperature-elevated NMR carbon spectrum of the polyethylene prepared in Example 9b) of the present invention.

[0050] Figure 5This is the temperature-elevated NMR carbon spectrum of the polyethylene prepared in Example 13b) of the present invention.

[0051] Figure 6 Graph showing stress-strain curves of polyethylene samples prepared in Examples 5a) and 5e) of the present invention.

[0052] Figure 7 Graph showing stress-strain curves of polyethylene samples prepared in Examples 9a) and 9d) of the present invention.

[0053] Figure 8 13a) and 13d) of the present invention.

[0054] Fig. 9 The elastic recovery curves of the polyethylene samples prepared in Examples 5a) and 5e) of the present invention.

[0055] Fig.10 Graph showing the elastic recovery curves of the polyethylene samples prepared in Examples 9a) and 9d) of the present invention.

[0056] Fig.11 Graph showing the elastic recovery curves of the polyethylene samples prepared in Examples 13a) and 13d) of the present invention.

[0057] Fig.12 This is the infrared spectrum of the polyethylene prepared in Example 5a) of the present invention.

[0058] Fig.13 This is the infrared spectrum of the polyethylene prepared in Example 5e) of the present invention.

[0059] Fig.14 This is the infrared spectrum of the polyethylene prepared in Example 9a) of the present invention.

[0060] Fig.15 This is the infrared spectrum of the polyethylene prepared in Example 9d) of the present invention.

[0061] Fig.16 This is the infrared spectrum of the polyethylene prepared in Example 13a) of the present invention.

[0062] Fig.17 This is the infrared spectrum of the polyethylene prepared in Example 13d) of the present invention. DETAILED DESCRIPTION

[0063] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content recorded in the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the present invention equally.

[0064] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0065] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0066] Unless otherwise specified, the concentrations in the following examples are molar concentrations.

[0067] The relevant parameters of the polymers obtained in the following examples are measured:

[0068] The molecular weight and molecular weight distribution are determined by conventional high temperature GPC method;

[0069] Melting points were determined by conventional DSC methods;

[0070] The polymerization activity of the polymer was calculated according to the following formula: polymerization activity = polymer yield / (catalyst dosage·polymerization time);

[0071] Calculation of branching degree: Take 50 mg of the corresponding polymer, dissolve it in 5 mL of deuterated o-dichlorobenzene, and measure it at 110 °C 13 C NMR data; or after the polymer sample is made into a film to obtain a uniform sample strip, the branching degree is calculated by its infrared spectrum data (calculated according to the method recorded in the reference (T. Usami, S. Takayama, Polym. J. 16 (1984) 731-738));

[0072] The fracture strain and ultimate tensile stress are obtained by measuring the stress-strain curve data when the sample strip breaks at room temperature;

[0073] The elastic recovery (SR) is obtained by measuring DMA curve data at room temperature.

[0074] The structures of all the synthesized complexes described below were confirmed by infrared and elemental analysis.

[0075] As a preferred embodiment, the synthesis of the complex in the embodiment is carried out according to the following reaction equation:

[0076]

[0077] Example 1

[0078] Preparation of N,N'-bis(2-cyclopentyl-4,6-di(diphenylmethyl))butane-2,3-diimine nickel bromide (Ni1)

[0079] 2-Cyclopentyl-4,6-di(diphenylmethyl)aniline (0.198 g, 0.4 mmol), 2,3-butanedione (0.009 g, 0.1 mmol) and (DME)NiBr2 (0.031 g, 0.1 mmol) were added to glacial acetic acid (2.5 mL), stirred and heated under reflux at 120°C for 4 h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure, the residue was dissolved in a small amount of dichloromethane (1 mL) and a large amount of anhydrous ether (25 mL) was added for recrystallization, and the precipitate was separated by filtration, and the solid phase was washed with anhydrous ether for several times and dried to obtain 0.021 g of red powder, i.e. Ni1, with a yield of 17%.

[0080] The structural confirmation data are as follows:

[0081] FT-IR(cm -1 ):2954(w),2869(w),1644(w,v(C=N)),1578(m),1494(m),1448(m),1418(w),13 40(w),1265(w),1215(w),1186(w),1163(w),1077(w),1031(w),745(m),699(s).

[0082] Elemental analysis: C 78 H 72 Br2N2Ni(1255.95) Theoretical value: C, 74.59; H, 5.78; N, 2.23. Exp. value: C, 74.23; H, 6.01; N, 2.04.

[0083] Example 2

[0084] Preparation of N,N'-bis(2-cyclohexyl-4,6-di(diphenylmethyl))butane-2,3-diimine nickel bromide (Ni2)

[0085] 2-Cyclohexyl-4,6-di(diphenylmethyl)aniline (0.812 g, 1.6 mmol), 2,3-butanedione (0.034 g, 0.4 mmol) and (DME)NiBr2 (0.123 g, 0.4 mmol) were added to glacial acetic acid (10 mL), stirred and heated under reflux at 120°C for 4 h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure, the residue was dissolved in a small amount of dichloromethane (1 mL) and a large amount of anhydrous ether (25 mL) was added for recrystallization, and after the precipitate was generated, the solid-liquid separation was performed by filtering, and the solid phase was washed with anhydrous ether for several times and dried to obtain 0.327 g of red powder, i.e. Ni2, with a yield of 64%.

[0086] The structural confirmation data are as follows:

[0087] FT-IR(cm -1 ):2921(w),2850(w),1637(w,v(C=N)),1600(m),1495(m),1446(m),1368(m),12 60(w),1239(w),1215(w),1162(w),1077(w),1032(w),776(w),748(m),699(s).

[0088] Elemental analysis: C 80 H 76 Br2N2Ni (1284.00) Theoretical value: C, 74.83; H, 5.97; N, 2.18. Exp. value: C, 74.67; H, 6.22; N, 1.94.

[0089] The ether was diffused into the dichloromethane solution of the complex by slow diffusion at room temperature to grow a Ni2 single crystal suitable for X-ray measurement. In order to express more clearly, all hydrogen atoms in the molecular structure of the complex were not drawn when drawing with ORTEP. The perspective view of the crystal molecular structure is shown in the figure below. Figure 1 As shown, it has a symmetrical structure, and the coordinated atoms exhibit a distorted tetrahedral geometry around the nickel center.

[0090] Example 3

[0091] Preparation of N,N'-bis(2-cyclooctyl-4,6-di(diphenylmethyl))butane-2,3-diimine nickel bromide (Ni3)

[0092] 2-cyclooctyl-4,6-di(diphenylmethyl)aniline (0.214 g, 0.4 mmol), 2,3-butanedione (0.009 g, 0.1 mmol) and (DME)NiBr2 (0.031 g, 0.1 mmol) were added to glacial acetic acid (2.5 mL), stirred and heated under reflux at 120°C for 4 h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure, the residue was dissolved in a small amount of dichloromethane (1 mL) and a large amount of anhydrous ether (25 mL) was added for recrystallization, and the precipitate was separated by filtration, and the solid phase was washed with anhydrous ether for several times and dried to obtain 0.027 g of red powder, i.e. Ni3, with a yield of 20%.

[0093] The structural confirmation data are as follows:

[0094] FT-IR(cm -1):2919(w),2857(w),1644(w,v(C=N)),1593(m),1494(m),1447(m),1421( w),1345(w),1185(w),1078(w),1030(w),914(w),849(w),744(m),698(s).

[0095] Elemental analysis: C 84 H 84 Br2N2Ni (1340.11) Theoretical values: C, 75.29; H, 6.32; N, 2.09. Exp. values: C, 74.98; H, 6.44; N, 1.83.

[0096] Example 4

[0097] Preparation of N,N'-bis(2-cyclododecyl-4,6-bis(diphenylmethyl))butane-2,3-diimine nickel bromide (Ni4)

[0098] 2-Cyclododecyl-4,6-di(diphenylmethyl)aniline (0.237 g, 0.4 mmol), 2,3-butanedione (0.009 g, 0.1 mmol) and (DME)NiBr2 (0.031 g, 0.1 mmol) were added to glacial acetic acid (2.5 mL), stirred and heated under reflux at 120°C for 4 h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure, the residue was dissolved in a small amount of dichloromethane (1 mL) and a large amount of anhydrous ether (25 mL) was added for recrystallization, and after the precipitate was generated, the solid-liquid separation was performed by filtering, and the solid phase was washed with anhydrous ether for several times and dried to obtain 0.037 g of red powder, which was Ni4, with a yield of 25%.

[0099] The structural confirmation data are as follows:

[0100] FT-IR(cm -1 ):2920(w),2858(w),1639(w,v(C=N)),1594(m),1494(m),1445(m),1373(w),1 258(w),1212(w),1161(w),1075(w),1031(w),914(w),847(w),743(m),697(s).

[0101] Elemental analysis: C 92 H 100 Br2N2Ni (1452.33) Theoretical value: C, 76.09; H, 6.94; N, 1.93. Exp. value: C, 75.83; H, 7.03; N, 1.77.

[0102] The ether was diffused into the dichloromethane solution of the complex by slow diffusion at room temperature to grow a Ni4 single crystal suitable for X-ray measurement. In order to express more clearly, all hydrogen atoms in the molecular structure of the complex were not drawn when drawing with ORTEP. The perspective view of the crystal molecular structure is shown in Figure 2 As shown, it has a symmetrical structure, and the coordinated atoms exhibit a distorted tetrahedral geometry around the nickel center.

[0103] Example 5

[0104] Ethylene polymerization was catalyzed by combining Ni2 and cocatalyst EtAlCl2 (EADC) under high pressure (10 atm):

[0105] a) Under ethylene atmosphere, 25 mL of toluene was first injected into a 250 mL stainless steel autoclave equipped with a mechanical stirring device, followed by the addition of 25 mL of a toluene solution containing 1 μmol of the complex Ni2, followed by the addition of 25 mL of toluene, the mechanical stirring was turned on, and the speed was maintained at 400 revolutions per minute. When the temperature in the autoclave reached 30° C., according to the set Al / Ni=500:1 condition, the required amount (1.0 mL) of the cocatalyst EtAlCl2 solution (0.5 mol / L in n-hexane) was added, and 25 mL of toluene was continued to be added to make the total volume of the reaction solvent 100 mL, and then the reactor was pressurized to 10 atm with ethylene gas, and the polymerization reaction began. The polymerization reaction was carried out for 30 min at an operating temperature of 30° C. After the polymerization, the reaction was quenched by neutralizing with 10% hydrochloric acid-acidified ethanol solution, and the polyethylene product was obtained after precipitation. It was then washed with ethanol several times, filtered and collected, and dried to constant weight under vacuum at 50°C. 5.15 g of polyethylene elastomer product was weighed, and the polymerization activity reached 10.3×10 6 g(PE)mol(Ni) -1 h -1 The molecular weight of the obtained polymer is M w =8.22×10 5 g·mol -1 , molecular weight distribution M w / M n =2.9(M w is the weight average molecular weight, M n is the number average molecular weight), polymer T m =80.6℃(T m The value represents the melting temperature of the polyethylene product), branching degree: 73 / 1000C, breaking strain ε b =353%, the ultimate tensile stress is 6.98MPa, and the elastic recovery rate SR=47.4%.

[0106] Take 50 mg of the polymer obtained in Example 5a) and dissolve it in 5 mL of deuterated o-dichlorobenzene. 13 C NMR data. The signal was accumulated 2000 times, and the signal peak shift was between 10-40 (ppm), proving that the obtained polymer was polyethylene with branched chains, with a branching degree of 73 / 1000Cs, and the branches contained methyl (81.8%), ethyl (2.13%), propyl (4.79%), butyl (4.03%), pentyl (2.11%) and long chain branches (5.17%) (see the specific spectrum) Figure 3 ). The sample strips prepared after polymer film pressing in Example 5a) were subjected to infrared spectrum test. The specific spectrum is shown in Fig.12 According to the method recorded in the reference (T. Usami, S. Takayama, Polym. J. 16 (1984) 731-738), the branching degree data measured by high temperature nuclear magnetic carbon spectrum of the polymer sample in Example 5a) and the infrared spectrum at 1374.14 cm -1 The absorbance data at the position was used to determine the relationship between the degree of branching and absorbance, which was then used for the subsequent calculation of the degree of branching based on infrared data for other sample strips (i.e., Examples 5e), 9a), 9d), 13a) and 13d)).

[0107] The breaking strain and ultimate tensile stress are obtained by measuring the stress-strain curve data of the sample strip made of the polymer obtained in Example 5a) at room temperature when it breaks. The breaking strain ε b is 353%, and the ultimate tensile stress is 6.98MPa (see the curve diagram Figure 6 Solid line). The elastic recovery rate (SR) is obtained by measuring the DMA curve data of the polymer sample strip obtained in Example 5a) at room temperature, and the elastic recovery rate is 47.4% (see the curve diagram Fig. 9 left side).

[0108] b) is basically the same as Example 5a), except that the polymerization operating temperature is 20°C and the polymerization activity reaches 7.74×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =12.5×10 5 g·mol -1 , molecular weight distribution M w / M n =2.9, polymer T m =104.6℃.

[0109] c) is basically the same as Example 5a), except that the polymerization temperature is 40°C and the polymerization activity reaches 9.68×10 6 g(PE)mol(Ni)-1 h -1 , polymer molecular weight M w =7.51×10 5 g·mol -1 , molecular weight distribution M w / M n =2.8, polymer T m =70.1℃.

[0110] d) is basically the same as in Example 5a), except that the polymerization temperature is 50°C and the polymerization activity reaches 9.24×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.66×10 5 g·mol -1 , molecular weight distribution M w / M n =2.7, compound T m =55.4℃.

[0111] e) is basically the same as in Example 5a), except that the polymerization temperature is 60°C and the polymerization activity reaches 6.60×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =4.64×10 5 g·mol -1 , molecular weight distribution M w / M n =2.7, polymer T m =46.3℃, the branching degree is 76 / 1000Cs (calculated by infrared spectrum data, see the specific spectrum Fig.13 ), fracture strain ε b =462%, the ultimate tensile stress is 4.29MPa, and the elastic recovery rate SR=61.6%.

[0112] The breaking strain and ultimate tensile stress are obtained by measuring the stress-strain curve data of the sample strip made of the polymer obtained in Example 5e) at room temperature when it breaks. The breaking strain ε b is 462%, and the ultimate tensile stress is 4.29MPa (see the curve Figure 6 The elastic recovery rate (SR) is obtained by measuring the DMA curve data of the polymer sample strip obtained in Example 5e) at room temperature, and the elastic recovery rate is 61.6% (see the curve diagram Fig. 9 on the right).

[0113] f) is basically the same as Example 5a), except that the polymerization operating temperature is 70°C and the polymerization activity reaches 2.26×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =3.89×10 5 g·mol -1 , molecular weight distribution M w / M n =2.6, polymer T m =44.5℃.

[0114] g) is basically similar to Example 5a), except that Al / Ni=300:1, i.e. 0.6 mL of the cocatalyst EtAlCl2 solution (0.5 mol / L in n-hexane). The polymerization activity reached 3.90×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.71×10 5 g·mol -1 , molecular weight distribution M w / M n =2.4, polymer T m =76.8℃.

[0115] h) is basically similar to Example 5a), except that Al / Ni=400:1, i.e. 0.8 mL of the cocatalyst EtAlCl2 solution (0.5 mol / L in n-hexane). The polymerization activity reached 6.56×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.74×10 5 g·mol -1 , molecular weight distribution M w / M n =3.1, polymer T m =68.5℃.

[0116] i) is basically similar to Example 5a), except that Al / Ni=600:1, i.e., 1.2 mL of the cocatalyst EtAlCl2 solution (0.5 mol / L in n-hexane). The polymerization activity reached 9.72×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =7.08×10 5 g·mol-1 , molecular weight distribution M w / M n =2.9, polymer T m =90.4℃.

[0117] j) is basically similar to Example 5a), except that Al / Ni=700:1, i.e., 1.4 mL of the cocatalyst EtAlCl2 solution (0.5 mol / L in n-hexane). The polymerization activity reached 9.12×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =6.68×10 5 g·mol -1 , molecular weight distribution M w / M n =2.9, polymer T m =73.7℃.

[0118] k) is basically similar to Example 5a), except that the polymerization solvent used is n-hexane and the polymerization activity reaches 1.56×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =8.42×10 5 g·mol -1 , molecular weight distribution M w / M n =2.8, polymer T m =99.7℃.

[0119] l) is basically similar to Example 5a), except that the polymerization time is 45 min and the polymerization activity reaches 9.48×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =10.1×10 5 g·mol -1 , molecular weight distribution M w / M n =2.8, polymer T m =82.2℃.

[0120] m) is basically similar to Example 5a), except that the polymerization time is 60 min and the polymerization activity reaches 9.24×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w=12.1×10 5 g·mol -1 , molecular weight distribution M w / M n =2.2, polymer T m =72.3℃.

[0121] Example 6

[0122] Ethylene polymerization was catalyzed by Ni1 and cocatalyst EtAlCl2 (EADC) under high pressure (10 atm):

[0123] The same as Example 5a), except that Ni1 was used as the main catalyst. The polymerization activity reached 8.60×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.35×10 5 g·mol -1 , molecular weight distribution M w / M n =2.6, polymer T m =103.4℃.

[0124] Example 7

[0125] The polymerization of ethylene was catalyzed by Ni3 and cocatalyst EtAlCl2 (EADC) under high pressure (10 atm):

[0126] The same as Example 5a), except that Ni3 was used as the main catalyst. The polymerization activity reached 0.26×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =4.37×10 5 g·mol -1 , molecular weight distribution M w / M n =2.2, polymer T m =85.6℃.

[0127] Example 8

[0128] Ethylene polymerization was catalyzed by combining Ni4 and cocatalyst EtAlCl2 (EADC) under high pressure (10 atm):

[0129] The same as Example 5a), except that Ni4 was used as the main catalyst. The polymerization activity reached 3.24×10 6 g(PE)mol(Ni) -1 h -1, polymer molecular weight M w =5.90×10 5 g·mol -1 , molecular weight distribution M w / M n =2.1, polymer T m =62.8℃.

[0130] Example 9

[0131] Use Ni2 and cocatalyst Et2AlCl (DEAC) to catalyze ethylene polymerization under high pressure (10atm):

[0132] a) Under ethylene atmosphere, 25 mL of toluene was first injected into a 250 mL stainless steel autoclave equipped with a mechanical stirring device, followed by the addition of 25 mL of a toluene solution containing 1 μmol of the complex Ni2, followed by the addition of 25 mL of toluene, the mechanical stirring was turned on, and the speed was maintained at 400 revolutions per minute. When the temperature in the autoclave reached 30° C., according to the set Al / Ni=500:1 condition, the required amount (1.0 mL) of the cocatalyst Et2AlCl solution (0.5 mol / L in toluene) was added, and 25 mL of toluene was continued to be added to make the total volume of the reaction solvent 100 mL, and then the reactor was pressurized to 10 atm with ethylene gas, and the polymerization reaction began. The polymerization reaction was carried out for 30 min at an operating temperature of 30° C. After the polymerization, the reaction was quenched by neutralizing with 10% hydrochloric acid-acidified ethanol solution, and the polyethylene product was obtained after precipitation. It was then washed several times with ethanol, filtered and collected, and dried to constant weight under vacuum at 50°C. 5.03 g of polyethylene elastomer product was weighed, and the polymerization activity reached 10.1×10 6 g(PE)mol(Ni) -1 h -1 The molecular weight of the obtained polymer is M w =9.98×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.5(M w is the weight average molecular weight, M n is the number average molecular weight), polymer T m =75.3℃(T m The value represents the melting temperature of the polyethylene product), and the degree of branching is 68 / 1000Cs (calculated by infrared spectrum data, see the specific spectrum Fig.14 ), fracture strain ε b =612%, the ultimate tensile stress is 10.72MPa, and the elastic recovery rate SR=48.9%.

[0133] The breaking strain and ultimate tensile stress are obtained by measuring the stress-strain curve data of the sample strip made of the polymer obtained in Example 9a) at room temperature when it breaks. The breaking strain ε b is 612%, and the ultimate tensile stress is 10.72Mpa (see the curve Figure 7 Solid line). The elastic recovery rate (SR) is obtained by measuring the DMA curve data of the polymer sample strip obtained in Example 9a) at room temperature, and the elastic recovery rate is 48.9% (see the curve diagram Fig.10 left side).

[0134] b) is basically the same as Example 9a), except that the polymerization temperature is 40°C and the polymerization activity reaches 10.7×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =8.85×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.5, polymer T m =63.7℃, degree of branching: 104 / 1000C.

[0135] Take 50 mg of the polymer obtained in Example 9b) and dissolve it in 5 mL of deuterated o-dichlorobenzene. 13 C NMR data. The signal was accumulated 2000 times, and the signal peak shift was between 10-40 (ppm), proving that the obtained polymer was polyethylene with branched chains, with a branching degree of 104 / 1000C, and the branches contained methyl (81.1%), ethyl (1.17%), propyl (3.93%), butyl (3.54%), pentyl (2.97%) and long chain branches (7.23%) (see the specific spectrum) Figure 4 ).

[0136] c) is basically the same as Example 9a), except that the polymerization temperature is 50°C and the polymerization activity reaches 7.16×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =7.97×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.4, polymer T m =55.8℃.

[0137] d) is basically the same as Example 9a), except that the polymerization operating temperature is 60°C and the polymerization activity reaches 6.66×106 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.50×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.2, polymer T m =44.0℃, the branching degree is 99 / 1000Cs (calculated by infrared spectrum data, see the specific spectrum Fig.15 ), fracture strain ε b =861%, the ultimate tensile stress is 8.59Mpa, and the elastic recovery rate SR=60.5%.

[0138] The breaking strain and ultimate tensile stress are obtained by measuring the stress-strain curve data of the sample strip made of the polymer obtained in Example 9d) at room temperature when it breaks. The breaking strain ε b is 861%, and the ultimate tensile stress is 8.59Mpa (see the curve diagram Figure 7 The elastic recovery rate (SR) is obtained by measuring the DMA curve data of the polymer sample strip obtained in Example 9d) at room temperature, and the elastic recovery rate is 60.5% (see the curve diagram Fig.10 on the right).

[0139] e) is basically the same as Example 9a), except that the polymerization operating temperature is 70°C and the polymerization activity reaches 6.40×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.09×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.2, polymer T m =38.8℃.

[0140] f) is basically similar to Example 9b), except that Al / Ni=300:1, i.e. 0.6 mL of the cocatalyst Et2AlCl solution (0.5 mol / L in n-hexane). The polymerization activity reached 3.24×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =6.30×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.4, polymer Tm =67.5℃.

[0141] g) is basically similar to Example 9b), except that Al / Ni=400:1, i.e. 0.8 mL of the cocatalyst Et2AlCl solution (0.5 mol / L in n-hexane). The polymerization activity reached 9.22×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =7.00×10 5 g·mol -1 , molecular weight distribution is M w / M n =3.3, polymer T m =63.7℃.

[0142] h) is basically similar to Example 9b), except that Al / Ni=600:1, i.e., 1.2 mL of the cocatalyst Et2AlCl solution (0.5 mol / L in n-hexane). The polymerization activity reached 9.74×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.56×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.6, polymer T m =62.2℃.

[0143] i) is basically similar to Example 9b), except that Al / Ni=700:1, i.e., 1.4 mL of the cocatalyst Et2AlCl solution (0.5 mol / L in n-hexane). The polymerization activity reached 5.54×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.43×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.6, polymer T m =65.9℃.

[0144] j) is basically similar to Example 9b), except that the solvent used for polymerization is n-hexane and the polymerization activity reaches 1.98×10 6 g(PE)mol(Ni) -1 h -1, polymer molecular weight M w =6.91×10 5 g·mol -1 , molecular weight distribution is M w / M n =2.2, polymer T m =51.9℃.

[0145] k) is basically similar to Example 9b), except that the polymerization time is 45 min and the polymerization activity reaches 7.92×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =10.1×10 5 g·mol -1 , molecular weight distribution M w / M n =2.3, polymer T m =66.9℃.

[0146] l) is basically similar to Example 9b), except that the polymerization time is 60 min and the polymerization activity reaches 6.43×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =10.9×10 5 g·mol -1 , molecular weight distribution M w / M n =2.5, polymer T m =66.4℃.

[0147] Example 10

[0148] Use Ni1 and cocatalyst Et2AlCl (DEAC) to catalyze ethylene polymerization under high pressure (10atm):

[0149] The same as Example 9b), except that Ni1 was used as the main catalyst. The polymerization activity reached 4.12×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =3.69×10 5 g·mol -1 , molecular weight distribution M w / M n =2.1, polymer T m =87.8℃.

[0150] Embodiment 11

[0151] Use Ni3 and cocatalyst Et2AlCl (DEAC) to catalyze ethylene polymerization under high pressure (10atm):

[0152] The same as Example 9b), except that Ni3 was used as the main catalyst. The polymerization activity reached 0.04×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =6.26×10 5 g·mol -1 , molecular weight distribution M w / M n =2.4, polymer T m =72.4℃.

[0153] Example 12

[0154] Use Ni4 and cocatalyst Et2AlCl (DEAC) to catalyze ethylene polymerization under high pressure (10atm):

[0155] The same as Example 9b), except that Ni4 was used as the main catalyst. The polymerization activity reached 0.30×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.29×10 5 g·mol -1 , molecular weight distribution M w / M n =2.4, polymer T m =51.9℃.

[0156] Example 13

[0157] Using Ni2 and co-catalyst MAO to catalyze ethylene polymerization under high pressure (10atm):

[0158] a) Under ethylene atmosphere, 25 mL of toluene was first injected into a 250 mL stainless steel autoclave equipped with a mechanical stirring device, followed by the addition of 25 mL of a toluene solution containing 1 μmol of the complex Ni2, followed by the addition of 25 mL of toluene, and mechanical stirring was turned on, maintaining a speed of 400 revolutions per minute. When the temperature in the autoclave reached 30° C., according to the set Al / Ni=2000:1 condition, the required amount (1.4 mL) of the cocatalyst MAO solution (1.45 mol / L in toluene) was added, and 25 mL of toluene was continued to be added to make the total volume of the reaction solvent 100 mL, and then the reactor was pressurized to 10 atm with ethylene gas, and the polymerization reaction began. The polymerization reaction was carried out for 30 min at an operating temperature of 30° C. After the polymerization, the reaction was quenched by neutralizing with 10% hydrochloric acid-acidified ethanol solution, and the polyethylene product was obtained after precipitation. It was then washed with ethanol several times, filtered and collected, and dried to constant weight under vacuum at 50°C. 3.57 g of polyethylene elastomer product was weighed, and the polymerization activity reached 7.14×10 6 g(PE)mol(Ni) -1 h -1 The molecular weight of the obtained polymer is M w =10.1×10 5 g·mol -1 , molecular weight distribution M w / M n =2.5(M w is the weight average molecular weight, M n is the number average molecular weight), polymer T m =93.0℃(T m The value represents the melting temperature of the polyethylene product), and the branching degree is 60 / 1000Cs (calculated by infrared spectrum data, see the specific spectrum Fig.16 ), fracture strain ε b =713%, the ultimate tensile stress is 15.91MPa, and the elastic recovery rate SR=47.9%.

[0159] The breaking strain and ultimate tensile stress are obtained by measuring the stress-strain curve data of the sample strip made of the polymer obtained in Example 13a) at room temperature when it breaks. The breaking strain ε b is 713%, and the ultimate tensile stress is 15.91MPa (see the curve diagram Figure 8 Solid line). The elastic recovery rate (SR) is obtained by measuring the DMA curve data of the polymer sample strip obtained in Example 13a) at room temperature, and the elastic recovery rate is 47.9% (see the curve diagram Fig.11 left side).

[0160] b) is basically the same as Example 13a), except that the polymerization temperature is 40°C and the polymerization activity reaches 13.2×106 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =9.68×10 5 g·mol -1 , molecular weight distribution M w / M n =2.0, polymer T m =66.5℃, degree of branching: 99 / 1000C.

[0161] Take 50 mg of the polymer obtained in Example 13b) and dissolve it in 5 mL of deuterated o-dichlorobenzene. 13 C NMR data. The signal was accumulated 2000 times, and the signal peak shift was between 10-40 (ppm), proving that the obtained polymer was polyethylene with branched chains, with a branching degree of 99 / 1000C, and the branches contained methyl (82.9%), ethyl (2.53%), propyl (6.01%), butyl (3.31%) and long chain branches (5.29%) (see the specific spectrum) Figure 5 ).

[0162] c) is basically the same as Example 13a), except that the polymerization operating temperature is 50°C and the polymerization activity reaches 11.6×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =7.95×10 5 g·mol -1 , molecular weight distribution M w / M n =2.1, polymer T m =54.6℃.

[0163] d) is basically the same as Example 13a), except that the polymerization operating temperature is 60°C and the polymerization activity reaches 7.82×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =7.24×10 5 g·mol -1 , molecular weight distribution M w / M n =2.1, polymer T m =43.4℃, the branching degree is 102 / 1000Cs (calculated by infrared spectrum data, see the specific spectrum Fig.17 ), fracture strain ε b=764%, the ultimate tensile stress is 9.02MPa, and the elastic recovery rate SR=71.2%.

[0164] The breaking strain and ultimate tensile stress are obtained by measuring the stress-strain curve data of the sample strip made of the polymer obtained in Example 13d) at room temperature when it breaks. The breaking strain ε b is 764%, and the ultimate tensile stress is 9.02MPa (see the curve diagram Figure 8 The elastic recovery rate (SR) is obtained by measuring the DMA curve data of the polymer sample strip obtained in Example 13d) at room temperature, and the elastic recovery rate is 71.2% (see the curve diagram Fig.11 on the right).

[0165] e) is basically the same as Example 13a), except that the polymerization operating temperature is 70°C and the polymerization activity reaches 6.54×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =5.75×10 5 g·mol -1 , molecular weight distribution M w / M n =1.9, polymer T m =36.7℃.

[0166] f) is basically similar to Example 13b), except that Al / Ni=1500:1, i.e. 1.0 mL of cocatalyst MAO solution (1.45 mol / L in toluene). The polymerization activity reached 9.50×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =9.33×10 5 g·mol -1 , molecular weight distribution M w / M n =2.0, polymer T m =70.2℃.

[0167] g) is basically similar to Example 13b), except that Al / Ni=1750:1, i.e. 1.2 mL of cocatalyst MAO solution (1.45 mol / L in toluene). The polymerization activity reached 11.7×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =10.4×10 5 g·mol -1, molecular weight distribution M w / M n =2.2, polymer T m =69.3℃.

[0168] h) is basically similar to Example 13b), except that Al / Ni=2250:1, i.e. 1.6 mL of cocatalyst MAO solution (1.45 mol / L in toluene). The polymerization activity reached 12.4×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =10.9×10 5 g·mol -1 , molecular weight distribution M w / M n =2.4, polymer T m =67.7℃.

[0169] i) is basically similar to Example 13b), except that Al / Ni=2500:1, i.e. 1.7 mL of cocatalyst MAO solution (1.45 mol / L in toluene). The polymerization activity reached 12.0×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =9.58×10 5 g·mol -1 , molecular weight distribution M w / M n =2.1, polymer T m =64.4℃.

[0170] j) is basically similar to Example 13b), except that the solvent used for polymerization is n-hexane and the polymerization activity reaches 2.08×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =7.11×10 5 g·mol -1 , molecular weight distribution M w / M n =2.0, polymer T m =57.1℃.

[0171] k) is basically similar to Example 13b), except that the polymerization time is 45 min and the polymerization activity reaches 11.4×10 6 g(PE)mol(Ni) -1 h -1, polymer molecular weight M w =8.69×10 5 g·mol -1 , molecular weight distribution M w / M n =2.0, polymer T m =63.7℃.

[0172] l) is basically similar to Example 13b), except that the polymerization time is 60 min and the polymerization activity reaches 10.7×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =7.78×10 5 g·mol -1 , molecular weight distribution M w / M n =2.0, polymer T m =62.1℃.

[0173] Embodiment 14

[0174] Using Ni1 and cocatalyst MAO to catalyze ethylene polymerization under high pressure (10atm):

[0175] The same as Example 13b), except that Ni1 was used as the main catalyst. The polymerization activity reached 5.78×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =8.22×10 5 g·mol -1 , molecular weight distribution M w / M n =2.0, polymer T m =91.1℃.

[0176] Embodiment 15

[0177] Using Ni3 and co-catalyst MAO to catalyze ethylene polymerization under high pressure (10atm):

[0178] The same as Example 13b), except that Ni3 was used as the main catalyst. The polymerization activity reached 0.52×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =15.0×10 5 g·mol -1 , molecular weight distribution M w / Mn =2.0, polymer T m =78.2℃.

[0179] Example 16

[0180] Using Ni4 and cocatalyst MAO to catalyze ethylene polymerization under high pressure (10atm):

[0181] The same as Example 13b), except that Ni4 was used as the main catalyst. The polymerization activity reached 4.18×10 6 g(PE)mol(Ni) -1 h -1 , polymer molecular weight M w =12.2×10 5 g·mol -1 , molecular weight distribution M w / M n =2.1, polymer T m =49.4℃.

[0182] The above description describes the embodiments of the present invention in ethylene polymerization in detail. However, the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nickel complex as shown in the following formula (I): in, R is the same or different, and each is independently selected from cyclopentyl, cyclohexyl, cyclooctyl or cyclododecyl; X is the same or different, and each is independently selected from F, Cl, Br or I.

2. The nickel complex of formula (I) according to claim 1, wherein The nickel complex represented by the formula (I) is selected from the following nickel complexes: Nickel complex 1: wherein R is cyclopentyl and X is Br; Nickel complex 2: R is cyclohexyl and X is Br; Nickel complex 3: R is cyclooctyl and X is Br; Nickel complex 4: wherein R is cyclododecyl and X is Br.

3. The method for preparing the nickel complex of formula (I) as claimed in claim 1, comprising the following steps: The compound represented by formula (II), the compound represented by formula (III) and the nickel-containing compound are mixed and stirred in a solvent to react to obtain the nickel complex represented by formula (I). wherein R and X are as defined in claim 1.

4. The method for preparing the nickel complex of formula (I) according to claim 3, wherein: The nickel-containing compound is selected from nickel-containing halides, hydrates or solvates of nickel-containing halides; The solvent is a weakly acidic organic solvent.

5. The method for preparing the nickel complex of formula (I) according to claim 4, wherein: The nickel-containing compound is selected from NiCl2·6H2O or NiBr2·DME; The solvent is formic acid or acetic acid.

6. A method for preparing a nickel complex represented by formula (I) according to any one of claims 3 to 5, wherein: The molar ratio of the compound represented by formula (II) to the compound represented by formula (III) is 1:(2-4); The molar ratio of the nickel-containing compound to the compound represented by formula (II) is 1:(1-1.5); The molar volume ratio of the compound represented by formula (II) to the solvent is 1:(25-100).

7. A method for preparing a nickel complex represented by formula (I) according to any one of claims 3 to 5, wherein: The reaction temperature is 60-120°C; the reaction time is 4-6 hours.

8. The method for preparing the nickel complex of formula (I) according to claim 7, wherein: The reaction temperature is 110-120°C.

9. A method for preparing a nickel complex represented by formula (I) according to any one of claims 3 to 5, wherein: The reaction is carried out under anaerobic conditions.

10. A method for preparing a nickel complex represented by formula (I) according to any one of claims 3 to 5, wherein: After the reaction is completed, the reaction solution is concentrated under reduced pressure to remove the solvent to obtain a residue, which is dissolved with a good solvent and then recrystallized by adding a poor solvent to precipitate a solid, which is filtered, washed and dried to obtain the product.

11. The method for preparing the nickel complex of formula (I) according to claim 10, wherein: The volume ratio of good solvent to poor solvent is 1:10-1:50; The good solvent is toluene or dichloromethane; the poor solvent is ether, n-hexane or n-heptane.

12. The method for preparing the nickel complex of formula (I) according to claim 11, wherein: The good solvent is dichloromethane; the poor solvent is anhydrous ether.

13. A catalyst composition comprising a main catalyst and an optional co-catalyst, wherein: The main catalyst is a nickel complex represented by formula (I) as claimed in claim 1 or 2.

14. The catalyst composition according to claim 13, wherein The co-catalyst is selected from one or more of aluminoxane, alkylaluminum and alkylaluminum chloride.

15. The catalyst composition according to claim 14, wherein The aluminoxane is methylaluminoxane and / or triisobutylaluminum-modified methylaluminoxane, the alkylaluminum is trimethylaluminum, and the alkylaluminum chloride is one or more of diethylaluminum monochloride, triethylaluminum trichloride or ethylaluminum dichloride.

16. The catalyst composition according to any one of claims 13 to 15, wherein When the catalyst composition includes a co-catalyst, the molar ratio of the metal Al in the co-catalyst to the central metal Ni of the nickel complex represented by formula (I) is (200-3000):

1.

17. The catalyst composition according to claim 16, wherein When the catalyst composition includes a co-catalyst, the molar ratio of the metal Al in the co-catalyst to the central metal Ni of the nickel complex represented by formula (I) is (300-2500):

1.

18. The catalyst composition according to claim 16, wherein When the co-catalyst is aluminoxane, the molar ratio of the metal Al in the co-catalyst to the central metal Ni of the nickel complex represented by formula (I) is (1500-2500):1; When the co-catalyst is alkylaluminum chloride, the molar ratio of the metal Al in the co-catalyst to the central metal Ni of the nickel complex represented by formula (I) is (300-700):

1.

19. A method for preparing polyethylene, comprising: Under the action of the catalyst composition as described in any one of claims 13 to 18, ethylene polymerization reaction is carried out to obtain polyethylene.

20. The method for preparing polyethylene according to claim 19, wherein: The polymerization reaction temperature is 20-70° C.; the polymerization reaction time is 5-120 min; and the polymerization reaction pressure is 0.3-20 atm.

21. The method for preparing polyethylene according to claim 19 or 20, wherein: The solvent used in the polymerization reaction is selected from one or more of toluene, o-xylene, n-hexane or cyclohexane.

22. The method for preparing polyethylene according to claim 21, wherein: The solvent used in the polymerization reaction is toluene.

23. Use of the nickel complex represented by formula (I) as claimed in claim 1 or 2 in the preparation of polyolefins.

24. Use according to claim 23, wherein the polyolefin is polyethylene.

Citation Information

Patent Citations

  • 4,4'-difluorobenzhydryl containing asymmetric alpha-diimine nickel complex, and intermediate, preparation method and application thereof

    CN106632506A

  • Nitryl asymmetric alpha-diimine nickel complex for preparation of ultrahigh-molecular-weight polyethylene and preparation method and application of nitryl asymmetric alpha-diimine nickel complex

    CN108794544A